2008
DOI: 10.1016/j.bcp.2008.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Deregulated expression of pro-survival and pro-apoptotic p53-dependent genes upon Elongator deficiency in colon cancer cells

Abstract: b i o c h e m i c a l p h a r m a c o l o g y 7 5 ( 2 0 0 8 ) 2 1 2 2 -2 1 3Abbreviations: B2M, beta-2-microglobulin; BARD1, BRCA1-associated RING domain 1; BAX, BCL2-associated X protein; BTG2, B-cell translocation gene 2; CDK9, cyclin-dependent kinase 9; DMEM, Dulbecco's modified Eagle's medium; DUSP4, dual-specificity phosphatase 4; Elp, Elongator protein; EMEM, Eagle's modified essential medium; FACT, facilitates chromatin transcription; GFP, green fluorescent protein; HA, haemagglutinin; hELP1, human ELP1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…Increased cell death at the same developmental stage leading to developmental delay was also reported in embryos lacking the human Bloom syndrome gene [46]. Also, further support for a putative role of IKAP in regulation of cell death or proliferation is enhanced by the findings that elimination of IKAP in vitro enhances basal expression of pro-apoptotic p53-dependent genes [47] and decreases expression of genes involved in cell proliferation [17].…”
Section: Discussionmentioning
confidence: 62%
“…Increased cell death at the same developmental stage leading to developmental delay was also reported in embryos lacking the human Bloom syndrome gene [46]. Also, further support for a putative role of IKAP in regulation of cell death or proliferation is enhanced by the findings that elimination of IKAP in vitro enhances basal expression of pro-apoptotic p53-dependent genes [47] and decreases expression of genes involved in cell proliferation [17].…”
Section: Discussionmentioning
confidence: 62%
“…We previously showed that Elongator deficiency actually slightly stabilized p53 in colon cancer-derived HCT116 cells, but that it did not impair DNA damage-induced p53 phosphorylation (52). We also demonstrated that some p53 target genes were aberrantly expressed upon Elongator deficiency, which indicated that this acetylase complex protects cells from an inappropriate expression of p53-dependent genes rather than promoting p53 activation.…”
Section: Discussionmentioning
confidence: 93%
“…IKAP-depletion has been shown to increase levels of pro-apoptotic genes such as Bax in colon cancer-derived cells and to alter levels of a number of pro-apoptotic genes in FD stem cells [41], [42] and may explain the developmental delay and early death observed in IKAP null mice [40]. Yeast two hybrid studies have identified binding of IKAP/Elp1 to BAT-3, an apoptosis regulatory gene [43].…”
Section: Discussionmentioning
confidence: 99%